Effect of mangosteen peel extract combined with demineralized freezed-dried bovine bone xenograft on osteoblast and osteoclast formation in post tooth extraction socket - Utari Kresnoadi; Yurike Hadisoesanto; Harly Prabowo (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Tooth extraction, a common procedure in dentistry, can cause bone resorption during socket healing. Therefore, it is important to perform socket preservation procedure to maintain alveolar bone. Providing a combination of mangosteen peel extract with demineralized freezed-dried bovine bone xenograft (DFDBBX) in tooth extraction socket was expected to accelerate alveol bone formation. Purpose: This study aims to determine the effect of mangosteen peel extract combined with DFDBBX introduced into the socket of post tooth extraction on the formation of osteoblasts and osteoclasts. Method: Twenty-eight (28) Cavia cobayas were divided into four groups. Extraction to the lower left incisor of Cavia cobaya was performed. The extraction socket was filled with 25 gram of PEG (group I) as a control, active materials consisted of mangosteen peel extract and DFDBBX 0.5% (group II), active materials consisted of mangosteen peel extract and DFDBBX 1% (group III), and active materials consisted of mangosteen peel extract and DFDBBX 2% (group IV). After thirty days, those Cavia cobayas were sacrificed. By using HE on Histopatological examination, the number of osteoblasts and osteoclasts were measured by light microscope with 400 times of magnification. The statistical analysis was then performed using oneway Anova & TukeyHSD test. Result: The component active materials consisted of mangosteen peel extract and DFDBBX 2% had the most significant results related to the formation of osteoblasts and osteoclasts. Conclusion: Mangosteen peel extract combined with DFDBBX can increase osteoblasts and decrease osteoclasts in the socket of tooth extraction in Cavia cobaya. The combination of mangosteen peel extract and DFDBBX 2% is the most effective material in increasing osteoblast and decreasing osteoclast.